2019
DOI: 10.21037/atm.2019.11.55
|View full text |Cite
|
Sign up to set email alerts
|

The disease burden of bronchiectasis in comparison with chronic obstructive pulmonary disease: a national database study in Korea

Abstract: Background: The prevalence and disease burden of bronchiectasis in comparison to those of chronic obstructive pulmonary disease (COPD) have not been well elucidated using a nationally representative database.Methods: We compared respiratory symptoms, physical activity, quality of life, and socioeconomic status in subjects with bronchiectasis versus those with COPD or control subjects participating in the Korea National Health and Nutrition Examination Survey 2007-2009. Participants were classified as physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…Extra-pulmonary comorbidities of bronchiectasis include many conditions such as connective tissue disease, inflammatory bowel disease, and immunodeficiency (9,13,14). In addition, low socioeconomic status and low family income were associated with bronchiectasis in subjects 40 years of age or older (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra-pulmonary comorbidities of bronchiectasis include many conditions such as connective tissue disease, inflammatory bowel disease, and immunodeficiency (9,13,14). In addition, low socioeconomic status and low family income were associated with bronchiectasis in subjects 40 years of age or older (12).…”
Section: Introductionmentioning
confidence: 99%
“…In several bronchiectasis cohort studies, patients with bronchiectasis were mainly elderly and females were more predominant than males (4)(5)(6). Previous pulmonary infectious conditions, such as pneumonia and tuberculosis (TB), chronic obstructive pulmonary disease (COPD), and asthma, are well established pulmonary comorbidities of bronchiectasis (7)(8)(9)(10)(11)(12). Extra-pulmonary comorbidities of bronchiectasis include many conditions such as connective tissue disease, inflammatory bowel disease, and immunodeficiency (9,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Y ang et al . [ 21 ] showed that the prevalence of bronchiectasis in subjects aged 40 or more years was 0.8%, which was based on the 2007–2009 Korean National Health and Nutrition Examination Survey database. However, there was a possibility of recall bias and exclusion of patients with severe symptoms and inability to respond to the survey.…”
Section: Discussionmentioning
confidence: 99%
“…It was based on the 2012-2017 Health Insurance Review and Assessment Service, National Patient Sample (HIRA-NPS) database and the ICD-10 diagnostic code, which could underestimate the true prevalence of bronchiectasis. A study by Yang et al showed that the prevalence of bronchiectasis in subjects aged 40 or more years was 0.8%, which was based on the 2007-2009 Korean National Health and Nutrition Examination Survey database[21]. However, there was a possibility of recall bias and exclusion of patients with severe symptoms and inability to respond to the survey.…”
mentioning
confidence: 99%
“…COPD patients who frequently experience exacerbations have adverse impacts on their life quality, spirometry function, and prognosis [ 4 ]. Moreover, exacerbation also increases social and financial costs [ 5 , 6 ]. Consequently, effective and timely prevention of COPD exacerbation is of great significance for patients and medical workers.…”
Section: Introductionmentioning
confidence: 99%